Empowering Moral Resilience: Psychoeducational Approaches in Disaster-Affected Communities - Siregar, Nurmaida Irawani; Lubis, Saiful Akhyar; Lubis , Lahmuddin (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
This study explores the role of psychoeducation in reinforcing moral development and psychological resilience among the residents of Sibanggor Julu Village, Puncak Sorik Marapi District, Mandailing Natal Regency, following a disaster. The research employs a qualitative, naturalistic approach to capture the complexities of community recovery through in-depth interviews, participant observations, and document analysis. Data validity was ensured through multiple strategies, including credibility, transferability, dependability, and confirmability. The key findings reveal that psychoeducational reinforcement significantly contributed to the villagers’ post-disaster recovery, leading to enhanced optimism, stronger family economic aspirations, increased religiosity, and improved psychological strength. The villagers also exhibited greater positive behavior and a revitalized fighting spirit. Furthermore, the study identifies the importance of structured psychoeducational activities, including professional human resources, ongoing support, and interactive learning methods such as games and environmental education, in fostering moral and psychological growth. Both exogenous factors (e.g., customs, education, environment, media) and endogenous factors (e.g., self-concept, personality) were found to influence the success of these interventions. The study’s findings highlight the effectiveness of psychoeducation in promoting moral development in post-disaster contexts. These insights offer valuable implications for the broader application of psychoeducational models in disaster recovery, suggesting that similar interventions could enhance community resilience and support moral regeneration in other affected areas globally.